Определение внутренних напряжений в цилиндрических деталях - Кобрин Михаил Моисеевич (Машиностроение, 1965)
Экземпляры: КХ (20190701) / Инвентарный номер: 396456 / Сис.шифр: 621.8 / Авт.знак: К 55 / ГРНТИ: 81 / ББК: 34